Study of relationship between adoption, knowledge and social-personal economic psychological and communication characteristic of wheat Growers of Panna block of Panna district (International Journal of Food and Nutritional Sciences, 2022)
This study investigates the intricate interplay between adoption rates of various practices, levelsof knowledge, and a spectrum of socio-personal, economic, psychological, and communicationcharacteristics within the context of Panna Block, situated in Panna District. With increasingemphasis on sustainable development and community empowerment, understanding thedynamics of adoption behaviors and their underlying determinants becomes imperative. Througha mixed-method approach comprising surveys, interviews, and observational studies, data wascollected from a diverse sample representing the demographic spectrum of the Panna Blockpopulation. The study identifies correlations between adoption rates and the socio-economicstatus of individuals, highlighting the role of education, income, and access to resources ininfluencing adoption behaviors. Furthermore, the analysis delves into the psychological factorssuch as attitudes, beliefs, and perceptions that shape individuals' willingness to adopt newpractices. Moreover, the study examines the role of interpersonal communication and communitynetworks in facilitating or hindering the spread of adoption.